SELF-EFFICACY DAN KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI TRIGONOMETRI SMA - ISLAMIATI, AYU DIAH (UNIVERSITAS TANJUNGPURA, 2025)
The goal of this study is to investigate the relationship between high school students' self-efficacy and capacity to solve trigonometric problems.This study is an example of correlational ex post facto research that was developed using a quantitative methodology. All of the research participants were in class XG SMA Negeri 8 Pontianak. The method entails giving a self-efficacy test and an essay-based assessment of a person's ability to solve math problems. The results showed that both the students' self-efficacy and their capacity for solving mathematical problems were in the middle range. To identify the association between the two variables, data analysis was performed. The data exhibits a linear correlation and is normally distributed. The Pearson Product Moment Test was then used to do a correlation analysis. The results of the tests were Sig.(2-tailed)